On the functional aspect of expressivity (with regards to contemporary printed publicistic texts) - Hradilova, Darina (Bohemica Olomucensia, 2012)
The main function of expressive words is not to express the author's feelings and attitudes, but to influence the recipient's feelings and attitudes. This fact is illustrated in the paper, concerning on the specific character of lexical expressivity in Czech as language that intensively derivates its new word formations.